Pilot Cohorts for Development of Concurrent Mobile Treatment for Alcohol and Tobacco Use Disorders - Alyssa M Medenblik; Patrick S Calhoun; Stephen A Maisto; Daniel R Kivlahan; Scott D Moore; Jean C Beckham; Sarah M Wilson; Dan V Blalock; Eric A Dedert (SAGE Publishing, 2021)
Alcohol and tobacco are the 2 most frequently used drugs in the United States and represent the highest co-occurrence of polysubstance use. The objective of this study was to refine an intervention combining mobile contingency management with cognitive-behavioral telephone counseling for concurrent treatment of alcohol and tobacco use disorders. Two cohorts (n = 13 total, n = 5 women) of participants were enrolled, with 10/13 completing treatment and 7/13 completing the 6-month follow-up. At enrollment, participants were drinking a mean of 28.9 drinks per week (SD = 14.1), with a mean of 14.7 heavy drinking days in the past month (SD = 9.9), and a mean of 18.1 cigarettes per day (SD = 11.7). Treatment included a mobile application that participants used to record carbon monoxide and breath alcohol content readings to bioverify abstinence. Participants received up to 4 sessions of phone cognitive-behavioral therapy and monetary reinforcement contingent on abstinence. In cohort 1, 4/6 participants reported abstinent or low-risk drinking post-monitoring. Six weeks post quit-date, 2/6 participants were CO-bioverified abstinent from tobacco use, with 2/6 in dual remission. These results were maintained at 6-months. In cohort 2, 6/7 reported abstinent or low-risk drinking post-monitoring, 5 weeks post quit-date. At the post-monitoring visit, 5/7 were CO-bioverified abstinent from smoking, with 5/7 in dual remission. At 6-months, 3/7 reporting abstinent or low-risk drinking, 1/7 had bioverified abstinence from smoking, with 1/7 in dual remission. Observations suggest that it is possible to develop a concurrent mobile treatment for alcohol and tobacco use disorders.